Monitoring the Rainwater Management Role to Solve Problem Related to Hydro- Environment Engineering - Laurentia, Susilawati Cicilia (Advanced Aspects of Engineering Research Vol. 1, 2021)
The problems related to hydro-environmental engineering on small islands are flood and drought, for the less favorable rainfall characteristics. Big rainfall intensity comes and flows immediately as storm runoff to the sea because of short distance, and no chance to infiltrate into the soil as ground-water recharge. Floods and landslides occur during rainy season and drought during dry season. Managing rainwater is an action to direct the runoff flow to be harvested and collected or conserved in accordance to the needs, and use it to meet the requirement. This research investigates the role of rainwater management in order to overcome these problems. The literature review and field observations of experiences on rainwater management techniques applied on both communal scale and household level. The water-trap series are intended to manage the flowing of the rainfall water through the river or natural drainage, as water conservation approach. The results show that firstly, rainwater must be managed in ways that small amount of rainwater flows out immediately to the sea. So, has chance to infiltrate into the soil as ground-water recharge. This is done by making some water-traps series, harvesting rainwater and storing it into the ponds at the household scale. The water then could be utilized for domestic and agriculture purposes. Secondly, learning from several experiences’ technology implementation as water conservation, it can be found the right way in managing rainwater of communal/household scale. These actions give the rainwater management have play role to solve problem related to hydro-environments engineering.